Biodistribusi radiofarmaka Tc99m DTPA pada pemeriksaan renografi - Dini Desita; Wahyu Setia Budi; Gani Gunawan (Youngster Physics Journal, 2017)
Reasearch about biodistribution on 25 patients with renography examination using the technique of in-vivo and in-vitro in nuclear medicine has conducted. The purpose of this reasearch is to determinate the value of activity on examination of kidney and bladder, determine biodistribution Tc99m DTPA on examination of the kidney and bladder, futhermore to determine biological half-life time in the kidney. Reasearch carried out by using radioisotope Tc99m with DTPA which carrier substances for examination of the kidney. Renography examination is done by injecting Tc99m DTPA intravenously into the patient’s arm as much as 4 to 8 mCi conjuction with posterior imaging in the kidney area in 10 to 15 minutes by using a gamma camera. Based on percentage of activity in getting from both kidneys, the left kidney is higher in compared to the right kidney. As for the bladder in second patients increased very significant due to illness in patients with chronic renal failure so that the kidney function is not functioning properly and radiopharmaceutical absorbed more in the bladder. The results of biodistribution activity Tc99m DTPA percentage is high on the bladder. The results obtained from the average half-life time (0,235 ± 0,001) hours. While the results of Tc99m DTPA effective half-life time in the body of each patient in the range of 0,5 to 2 hours. First patients has a longest biological half-life time. Differences in the effective half-life time of each patient is affected by the elimination of biological or biological half-life time of each patient is different too.Keywords: Tc99m, DTPA, renography, biodistribution, effective half-life time.